MEDICINAL ANALYSIS OF THE PLANT GLYCYRRHIZA GLABRA - Safokulov Bobur; Khusankhonov Azizkhon; Ayozov Shohabbos (TADQIQOTLAR, 2025)
Abstract Objective: Alternative medicine has an important place in the fight against many diseases  in  human  history.  The  biological  activity  of  Glycyrrhiza  glabra  L.  was investigated  in  this  study.  Material  and  Method:  The  root  parts  of  the  plant  were extracted with ethanol. Antioxidant and oxidant potentials were determined using Rel Assay  kits.  Antimicrobial  activity  was  tested  against  standard  bacteria  and  fungus strains using the agar dilution method. Antiproliferative activity was determined by MTT test against Lung Carcinoma Cell Line (A549). Result and Discussion: As a result of the studies, the TAS value of the plant was measured as 8.770±0.171, TOS value as 14.590±0.191  and  OSI  value  as  0.167±0.005.  Inhibition  of  the  plant  extract  was observed against standard bacteria and fungus strains at ranging from 50-200 µg/mL concentrations. In addition, it was determined that the plant extract displayed strong antiproliferative  activity  due  to  the  increase  in  concentration.  As  a  result  of  these studies,  it  has  been  determined that  G.  glabra  can  be used  as  an  important  natural antioxidant, antimicrobial and anticancer agent.